Recent advances in marine oligosaccharides: A review of bioactivities and application - Tongxiao Luan; Song Hu; Weihong Nie; Jia Liu; Shan Wang; Li Jia; Jing Zhou; Nina An; Yifan Wang; Ziwei Cui; Yongjun Mao (Journal of Functional Foods, 2023)
Marine polysaccharides are widely present in the marine algae and marine organisms making them easy to obtain. Moreover, marine polysaccharides attract global attention from scholars due to a wide range of biological activities. However, marine polysaccharides have drawbacks such as poor solubility and low bioavailability. Studies have shown that marine oligosaccharides, as the degradation products of marine polysaccharides, have good solubility and bioavailability while retaining the partial unique biological activity of marine polysaccharides. Herein, we summarize and categorize the biological activity and potential application of marine oligosaccharides in biomedicine. The biological activities of marine oligosaccharides in the digestive and immune systems are highlighted, along with brief descriptions in other organs and systems. In addition, the application of marine oligosaccharides in biological materials is emphasized, and their nutritional applications are roughly outlined. Finally, the review summarizes and prospects the applications of marine oligosaccharides in biomedicine.